Dietary roughage sources affect lactating Holstein x Zebu cows under experimental conditions in Brazil: a meta-analysis - Alessio D.R.M.* (2020)
© 2019, Springer Nature B.V.To reduce costs, lactating cows are often fed a higher proportion of roughage and alternative feeds; however, such protocols may not lead to optimal milk production. Using a meta-analysis, we evaluated the effects of dietary roughage sources on the composition, voluntary intake, and digestibility of diets fed to crossbred Holstein x Zebu cows under experimental feeding conditions in Brazil. Finally, we assessed the effects of dietary roughage sources on milk yield and composition. The database was composed of 43 experiments with 183 treatments, including 943 lactating cows. The data were obtained from studies published between January 2000 and December 2015. The data were evaluated by analysis of variance, considering the distribution of variables. The diets differed in dry matter and crude protein (CP) contents according to the roughage sources. Diets based on corn silage demonstrated higher intakes of neutral detergent fiber (NDF), CP, and total digestible nutrients, which improved the digestibility of NDF and CP, and resulted in a higher milk yield compared to the diets with one roughage source or those with a combination of two roughage sources. The present study demonstrated that feeding crossbred Holstein x Zebu lactating cows alternative roughage sources compromised milk production and that lactating cows produced higher milk yields when fed corn silage.